Nutritional Status, Sleep Duration and the Menstrual Cycle Among Adolescent Girls - Yusrima Syamsina Wardani; Tahirah Sakinatun Nisa; Lilik Hidayanti (Jurnal Ilmiah Kesehatan (JIKA), 2026)
Menstrual cycle regularity is an important indicator of reproductive health in adolescent girls. Irregular menstrual cycles are still commonly found and are suspected to be associated with lifestyle factors, particularly nutritional status and sleep duration. This study aimed to determine the relationship between nutritional status and sleep duration with menstrual cycles among female students at SMAN 10 Tasikmalaya. The study used an analytic observational design with a cross-sectional approach. Respondents were adolescent girls aged 16–18 years who had experienced menstruation. Nutritional status data were obtained through anthropometric measurements using body mass index-for-age, while information regarding sleep duration and menstrual cycles was collected through interviews using structured questionnaires. Data analysis was conducted using univariate and bivariate analyses with the Chi-Square test. The results showed that most respondents with overweight nutritional status had normal menstrual cycles. In addition, adolescents with insufficient sleep duration tended to experience irregular menstrual cycles. Nutritional status and sleep habits was associated with menstrual cycle patterns among adolescent girls. Therefore, health education in the school environment regarding the importance of balanced nutrition and good sleep habits is needed to maintain adolescent reproductive health.